2020
DOI: 10.1002/jpen.1979
|View full text |Cite
|
Sign up to set email alerts
|

Nutrition and Gastrointestinal Dysmotility in Critically Ill Burn Patients: A Retrospective Observational Study

Abstract: Background Gastrointestinal (GI) dysmotility impedes nutrient delivery in critically ill patients with major burns. We aimed to quantify the incidence, timing, and factors associated with GI dysmotility and subsequent nutrition delivery. Methods A 10‐year retrospective observational study included mechanically ventilated, adult, critically ill patients with ≥15% total body surface area (TBSA) burns receiving nutrition support. Patients with a single gastric residual volume ≥250 mL were categorized as having GI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…Early EN stimulates intestinal contraction through direct contact between the nutrients and intestinal mucosal cells and is of great importance in weakening hypermetabolism, reducing circulating stress hormones, and protecting the integrity and function of the intestinal mucosa. A large number of studies have provided evidence that early EN reduces the risk of GI bleeding, sepsis and organ injury, shortening the LOHS [ 51 ]. Raff et al [ 52 ] reported that the risk of GI haemorrhage in severe burn patients treated with early EN was reduced by 40%.…”
Section: Discussionmentioning
confidence: 99%
“…Early EN stimulates intestinal contraction through direct contact between the nutrients and intestinal mucosal cells and is of great importance in weakening hypermetabolism, reducing circulating stress hormones, and protecting the integrity and function of the intestinal mucosa. A large number of studies have provided evidence that early EN reduces the risk of GI bleeding, sepsis and organ injury, shortening the LOHS [ 51 ]. Raff et al [ 52 ] reported that the risk of GI haemorrhage in severe burn patients treated with early EN was reduced by 40%.…”
Section: Discussionmentioning
confidence: 99%
“…Major burns standard nutrition recommendation of very early enteral nutrition initiation and caloric goal achievement in a week [16][17][18] might not success in every case. 19 PN is one of the options to supply calories to reach daily goal in enteral intolerance and offer some specific nutrients support. For energy providing purpose, it can be used as partial caloric supplement or main supply source of daily energy requirement.…”
Section: Discussionmentioning
confidence: 99%
“…The studies included 10 prospective studies [ [114] , [115] , [116] , [117] , [118] , [119] , [120] , [121] , [122] , [123] ] and 16 retrospective studies. [ [124] , [125] , [126] , [127] , [128] , [129] , [130] , [131] , [132] , [133] , [134] , [135] , [136] , [137] , [138] , [139] ] The overall incidence rate of feeding intolerance in critically ill patients was found to be 0.40 (95% CI: 0.34 to 0.46), indicating a substantial association with adverse patient-centered outcomes. Particularly noteworthy is the OR for all-cause ICU mortality risk, which was 1.99 (95% CI: 1.69 to 2.35).…”
Section: Guidelines For Responses To Clinical Questions and Evidencementioning
confidence: 99%